PUBLIC LIBRARY DESIGN WITH THE APPLICATION OF INCLUSIVE ARCHITECTURE IN TARUTUNG - Suwanntoro, Hajar; Hutauruk, Mathias Harun Bungaran (Komunitas Menulis dan Meneliti (Kolibi), 2024)
The library is a place that is in charge and responsible for the availability of complete information and the provision of fast services according to information needs, so that when accessed users can be satisfied in searching for information. Currently, libraries are starting to be displaced by modern times. Instead of being a place to get information to broaden your knowledge, now they are starting to be displaced by digital technology, such as cellphones, laptops, TV, and other technology, which are more interesting, informative and can be accessed by people. anyone, including people with disabilities. This is clearly illustrated in the regional library of North Tapanuli district, specifically the one in Tarutung, which is not well organized, uncomfortable, unable to facilitate the large number of users and still uses print media as a source of information which results in a lack of interest in reading, especially for children and teenagers. , and is not accessible to everyone, including individuals with disabilities. Therefore, it is necessary to relocate and redevelop the public library in the city of Tarutung through values in architecture with inclusive design as a process to make the public library a public area accessible to everyone and capable of transforming a multi-purpose space that integrates with the environment so that it will support increasing public literacy with good public library planning.